Tumors of dogs between the years 1985-1992 in konya - Hüdaverdi Erer; Metin Münir Kıran (Eurasian Journal of Veterinary Sciences)
In this survey, 27 dogs with a total of 34 neoplasms were examined in the department of Pathology, Veterinary Faculty, University of Selçuk from January 1985, to December, 1992. Female genita/ system was the most frequently affected body system (44. 1 %) [particularly mammary gland (32.4 %)} this fo/lowed by cutaneous (23. 6 %), ma/e gen it al system (14. 7%) and a/imentary system (11.8 %} tumors. Out of 27 dogs, primary multiple tumors were detected in 4 cases (14.8%).